"Me ollaan mukana tässä experimentissä" : lingvististiska resurser och språkpraktiker i tvåspråkiga ungdomssamtal i Haparanda, Stockholm och Helsingfors - Kolu, Jaana (University of Jyväskylä, 2017)
The thesis explores bilingual adolescents’ language use, linguistic resources, and language practices in interaction at three junior high schools in Haparanda, a Swedish town on the country’s northeastern border with Finland. A comparison is also made with interaction among bilingual adolescents at two Sweden-Finnish junior high schools in Stockholm and at one Swedish-speaking junior high school in Helsinki. The aim of the study is to increase our knowledge of bilingual adolescents’ interaction practices and language repertoires, i.e. translanguaging, in interaction. The primary data consists of close to eleven hours of video- and audio-recorded informal group and pair conversations. The data was collected in 2014–2015 among 14–15-year-old bilingual adolescents at three junior high schools in Haparanda. The first set of material for comparison, comprising six hours of bilingual 13–15-year-old adolescents’ informal conversations, was collected in 2014 at a Swedish junior high school in Helsinki. The second set consists of 8 hours of video- and audio-recorded group conversations among 13–15-year-old bilingual adolescents in two Sweden-Finnish high schools in Stockholm in 2015–2016. Each of the conversations lasted for between fifteen minutes and one and a half hours. The theoretical framework is found in the field of translanguaging, which aims to describe bilingual language use and interactional practices (including code-switching), rather than focusing on the languages themselves. In translanguaging, research on interaction has the multilingual speaker, not the monolingual individual, as the norm. The analysis of the conversation data collected is mainly qualitative. The qualitative analysis of the bilingual adolescents’ conversations in Haparanda reveals patterns in their use of linguistic resources and translanguaging practices in interaction. The interlocutors fluidly and flexibly make use of their language resources, including grammar, morphology, syntax and language practices in their interaction. Not only ...